The Role of Big Rating Agencies in Intensifying the Economic Crises - PETRU FILIP (Global Economic Observer)
Fitch, Standard & Poor's (S&P) and Moody's are the three big rating agencies on the planet, representing some of the strongest protagonists in the world of financing. Concretely, these three big rating agencies evaluate the creditworthiness of both companies and the countries requesting this, with the aim of giving the investors and idea concerning the investments to be made in the safest way. AAA is the highest rating granted by these agencies. Then follows the AA1 and the scale goes down to C. Any rating at/or below BBB is known as “junk” (trash). The more diminished the evolution perspectives granted by the rating agencies, the more a firm or a country gets closer to the state of payment incapacity of its debts. Thus there are indirectly intensified the economic crises. Creditors that keep on lending the respective country or firm are less optimistic with regard to the perspectives of getting their money back- and thus they shall levy higher interest rates. The higher the interest rates, the more difficult the reimbursing of debts or of the firm, or the government is to be made and it is more likely that this falls within payment incapacity.